2021
DOI: 10.1021/acs.nanolett.1c00076
|View full text |Cite
|
Sign up to set email alerts
|

Single-Atom-Based Heterojunction Coupling with Ion-Exchange Reaction for Sensitive Photoelectrochemical Immunoassay

Abstract: Benefiting from the maximum atom-utilization efficiency and distinct structural features, single-atom catalysts open a new avenue for the design of more functional catalysts, whereas their bioapplications are still in their infancy. Due to the advantages, platinum single atoms supported by cadmium sulfide nanorods (Pt SAs-CdS) are synthesized to build an ultrasensitive photoelectrochemical (PEC) biosensing platform. With the decoration of Pt SAs, the PEC signal of CdS is significantly boosted. Furthermore, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(61 citation statements)
references
References 56 publications
0
61
0
Order By: Relevance
“…As abovementioned, current OECT sensors have exclusively resorted to two existing sensing interfaces (channel/electrolyte and gate/electrolyte), this work created additional interfaces of LA/electrolyte and RA/electrolyte to accommodate the sensing events. In light of the prevalent usage of copper ion (Cu 2+ ) as signaling species, [ 38,49–52 ] the feasibility was exemplified by interaction between n‐type semiconductors CdS/TiO 2 and Cu 2+ , which could yield lower K sp product and inhibit the signal. As shown in Figure a and inset, the “n/‐” combination was initially tested for real‐time monitoring Cu 2+ .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As abovementioned, current OECT sensors have exclusively resorted to two existing sensing interfaces (channel/electrolyte and gate/electrolyte), this work created additional interfaces of LA/electrolyte and RA/electrolyte to accommodate the sensing events. In light of the prevalent usage of copper ion (Cu 2+ ) as signaling species, [ 38,49–52 ] the feasibility was exemplified by interaction between n‐type semiconductors CdS/TiO 2 and Cu 2+ , which could yield lower K sp product and inhibit the signal. As shown in Figure a and inset, the “n/‐” combination was initially tested for real‐time monitoring Cu 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…[ 30–32 ] On the other hand, photoelectrochemistry (PEC), [ 33–35 ] making use of photon‐to‐electricity conversion, has enabled non‐contact, remote‐controlled, and even self‐powered operation of various semiconductor devices interfacing the biological world. [ 36–39 ] Synergizing with PEC, BPE should also have unparalleled prospect due to its high compatibility with light and semiconductor species. Biorthogonal control of light with spatiotemporal resolution in the integrated system is further expected to promote the development of advanced optoelectronics such as OPECT.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] Because of the different forms of light input and electrical output, the advantage of reduced background signal makes this methodology inherently more sensitive than conventional electrochemical detection methods. [20] Extensive research work on advanced PEC bioanalysis hithero reported has generally been carried out along two directions, 1) development of high performance photoactive materials as transducers and their integration with biological species, [21,22] and 2) developing novel mechanisms for signal generation and transduction. [23][24][25] Currently, for the important signal amplification in PEC bioanalysis, major efforts have been devoted to various biological routes, such as enzymatic catalysis and nucleic acid-based amplification technologies.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 PSA is a protein produced by the prostate gland. 5 High PSA levels in the blood are a sign of prostate cancer. Generally, we believe that the risk of prostate cancer will increase conspicuously when the concentration of PSA exceeds the internationally recognized level (<4.0 ng•mL −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, it is a matter of cardinal significance to quickly and precisely diagnose prostate cancer. Prostate-specific antigen (PSA) as a biomarker for prostate cancer monitoring is still accepted extensively on a troubleshooting implementation. , PSA is a protein produced by the prostate gland . High PSA levels in the blood are a sign of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%